FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KETIDAKPATUHAN PENDERITA TUBERKULOSIS DALAM BEROBAT DI POLIKLINIK DOTS RSUP SANGLAH DENPASAR - Bagiada, I Made; Putri Primasari, Ni Luh (journal of internal medicine, 2010)
Tuberculosis (TB) is a major public health problem in the world, especially in developing countries such as Indonesia. Itremains a major contributor to the global burden of disease and has received considerable attention in recent years, particularlyin developing countries. In our country, there is a little information about factors that can predict the adherence of TB patients.The objective of this study was to know factors contributing in non-adherence TB patients in polyclinic DOTS RSUP SanglahDenpasar. This study was a cross-sectional descriptive study of 15 adult newly diagnosed TB patients. Patients interviewed withquestionnaires consist of demographic and reasons of their non-adherence for TB treatment. About 12 (80%) of TB patients weremale. We didn?t ! nd much different in knowledge, work, educational status, and home distance among TB patients to in" uencethe adherence of the patients. The most important factor in" uencing the adherence of TB patients were drug side effects. Thedrug side effects were gastritis and skin itch (found in 10 and 3 patient respectively). Another reason for non-adherence in TBtreatment were over estimated and cost.Adherence was one of the potential factors to increase cure rate in TB patients. Non- adherence not only decreasing curerate in TB patients, but also as a risk for MDR TB. By determining inhibition factors in the treatment of TB patients, we canimprove the effectiveness of TB treatment.